Basic Engineering for Medics and Biologists - Lee, T. Clive (IOS Press, 2013)
Developments in bioengineering and medical technology have led to spectacular progress in clinical medicine. As a result, increased numbers of courses are available in the area of bioengineering and clinical technology. These often include modules dealing with basic biological and medical sciences, aimed at those taking up these studies who have a background in engineering. To date, relatively few participants from medicine have taken up courses in biomedical engineering, to the detriment of scientific exchange between engineers and medics. The European Society for Engineering and Medicine (ESEM) aims to bridge the gap between engineering and medicine and biology. It promotes cultural and scientific exchanges between the engineering and the medical/biological fields. This primer consists of a series of First Step chapters in engineering and is principally presented for those with a medical or biology background who intend to start a MSc programme in biomedical engineering and for medics or biologists who wish to better understand a particular technology. It will also serve as a reference for biomedical engineers. Written by engineers and medics who are leaders in their field, it covers the basic engineering principles underpinning: biomechanics, bioelectronics, medical informatics, biomaterials, tissue engineering, bioimaging and rehabilitation engineering. It also includes clinically relevant examples.